THE CONCEPT OF THE DEVELOPMENT OF THE UKRAINIAN AIC ON THE PRINCIPLES OF THE “GREEN” ECONOMY - TOKARCHUK, Dina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to the study of the conceptual foundations of the development of the agro-industrial complex of Ukraine on the basis of the “green” economy as an integrative model capable of ensuring the sustainable functioning of the sector in the conditions of climate change, resource depletion and geopolitical challenges. The popularity of the concepts of “green”, circular and bioeconomy in search queries and scientific works is studied; despite the dominance of the circular economy, interest in the green economy has grown the most in recent years.A comparison of three interrelated models – “green”, circular and bioeconomy – is carried out in order to identify their key principles, implementation tools, spheres of influence and role in the agricultural sector. It is substantiated that the “green” economy, as a strategic paradigm, combines environmental sustainability, economic efficiency and social inclusion, creating a basis for the modernization of the agro-industrial complex in accordance with European standards, in particular, in accordance with the European Green Deal. It was found that the “green” economy is the most universal model, as it combines approaches to the efficient use of resources (including secondary) and the introduction of biotechnological innovations.The Concept of the Development of the Ukrainian AIC on the Principles of the “Green” Economy is proposed, which provides for the introduction of precision agriculture, bioenergy technologies, waste-free production processes, “green” financial instruments, digital agricultural management and social orientation of the development of rural areas. The expected results of the Concept’s implementation are determined – reduction of greenhouse gas emissions, increase in the share of renewable energy, formation of environmentally responsible agribusiness and creation of new jobs. The emphasis is on the need for state support, institutional support and attraction of investments as prerequisites for a successful transition to a “green” AIC.
Keywords: “green” economy; agro-industrial complex; sustainable development; bioeconomy; circular economy; ecological transformation